Teun Van A Dijk's Critical Discourse Analysis Model in the online news "Reading Megawati's Political Communication Carelessness in the Cooking Oil Polemic" - Noviyanti, Anggi; Andriyanti, Erna; Ashadi, Ashadi (Journal of Literature Language and Academic Studies, 2024)
The controversy over the scarcity of cooking oil in Indonesia has made it difficult for all levels of society, from the lower, middle, and upper classes, to obtain cooking oil. With the scarcity of cooking oil, one of the fifth presidents in Indonesia, Megawati, commented and was featured in the Kompas.com news entitled "Membaca Kecerobohan Komunikasi Politik Megawati dalam Polemik Minyak Goreng". This research will focus on Megawati's response to determine how the discourse analysis process works. Critical analysis of news and the compass's alignment with Megawati in Teun A Van Dijk's theory. This qualitative research uses Van Dijk's critical discourse analysis model, which divides the analysis into three structures: macrostructure, super macrostructure and microstructure. The research results show that through model analysis theory, Teun A Van Dijk's systematic system can make it easier for researchers to find the background of the problem through macro analysis. From this analysis, Kompas tries not to offend Megawati with sentences that change the meaning. Kompas's position in the news is neutral, in the middle between Megawati and other sources.